EFFECT OF AGRICULTURAL OUTPUT AND FOOD SECURITY ON ECONOMIC GROWTH IN NIGERIA - Oke, M.A.; Ogunnubi, H.A.; Oladeji, I.O. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study assessed agricultural output, food security and economic growth in Nigeria. Time series data for 43 years (1981-2023) was obtained from the CBN bulletin Statistical bulletin (2023) and world bank development indicators. The study used the Auto Regressive Distributed Lag (ARDL) model for the regression. Results showed that the food production index, inflation agricultural expenditure had a positive short run and long run relationship with economic growth. Agricultural output on the other hand had a negative relationship with the economic growth in the long run. For the short run analysis, a 1% increase in the Food Production index (FPRI) will increase the GDP by 0.511% at 5% level of significance. The long run result shows that 1% rise in the FPRI increased GDP by 3.548% at a 1% level of significance. This shows that a rise in the food production index will increase economic growth in a nation with good security. In addition, a 1% increase in the Agricultural Output (AGO) will reduce the GDP by 0.050% but not significant (P = 0.236). The Granger causality test revealed no evidence of bidirectional causality between LFPRI and LGDP. Although LFPRI showed weak predictive power for LGDP at the 10% significance level (p = 0.079), LGDP did not Granger-cause LFPRI (p = 0.795). Furthermore, the results indicated a unidirectional causality running from LGDP to LAGO, as LGDP significantly Granger-caused LAGO (p < 0.01), while LAGO did not Granger-cause LGDP (p = 0.806). The researchers recommended that Nigeria should reduce her food imports and encourage local food production. The government should also increase the subsidies of inputs to farmers and increase the funding of the agricultural sector which will ensure food security, reduce unemployment, and increas incomes to the people.